2018
DOI: 10.1161/circinterventions.117.006000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronary Artery Revascularization Completeness on Outcomes of Patients With Coronary Artery Disease Undergoing Transcatheter Aortic Valve Replacement

Abstract: Background-Coronary artery disease (CAD) is highly prevalent in patients undergoing transcatheter aortic valve replacement.In the overall CAD population, complete revascularization or reasonable incomplete revascularization (ICR) is associated with improved outcomes; whether the same applies for the transcatheter aortic valve replacement population is still a matter of debate. Methods and Results-We conducted a systematic review and meta-analysis of studies that examined the prognostic effect of revascularizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…While a meta-analysis of 7 studies (2,472 patients) did not prove a mid-term effect of CAD on TAVR outcomes (116), a more recent one (15 studies, 8,013 patients) has shown no impact on 30-days mortality but a significant adverse impact on 1-year mortality (OR 1.21; 95% CI, 1.07-1.36; P=0.002) (117). In a third meta-analysis (6 studies, 3,107 patients), a residual SYNTAX (Synergy Between PCI With Taxus and Cardiac Surgery)-score cut-off value (<8) after coronary revascularization has been shown to predict a significantly higher mortality (OR 1.69; 95% CI, 1.26-2.28; P<0.001) (118). The eagerly awaited results from the ACTIVATION trial (ISRCTN75836930) (119) will help to establish recommendations about the need and appropriate extent of CAD revascularization prior to TAVR.…”
Section: Tavr and Cardiac Ischemic Diseasementioning
confidence: 99%
“…While a meta-analysis of 7 studies (2,472 patients) did not prove a mid-term effect of CAD on TAVR outcomes (116), a more recent one (15 studies, 8,013 patients) has shown no impact on 30-days mortality but a significant adverse impact on 1-year mortality (OR 1.21; 95% CI, 1.07-1.36; P=0.002) (117). In a third meta-analysis (6 studies, 3,107 patients), a residual SYNTAX (Synergy Between PCI With Taxus and Cardiac Surgery)-score cut-off value (<8) after coronary revascularization has been shown to predict a significantly higher mortality (OR 1.69; 95% CI, 1.26-2.28; P<0.001) (118). The eagerly awaited results from the ACTIVATION trial (ISRCTN75836930) (119) will help to establish recommendations about the need and appropriate extent of CAD revascularization prior to TAVR.…”
Section: Tavr and Cardiac Ischemic Diseasementioning
confidence: 99%
“…A recent pooled analysis demonstrated that patients undergoing TAVR with higher residual SYNTAX (Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery) score were at risk of greater subsequent mortality. 65 The importance of correctly identifying ischaemia-inducing lesions in such patients prompted the recent exploration of pressure-based indices in these cohorts. While the feasibility of both FFR and iFR has been demonstrated in such patients, there are concerns that the altered ventriculo-aortic physiology distorts their accuracy.…”
Section: Special Patient and Lesion Subgroupsmentioning
confidence: 99%
“…Using the residual SYNTAX score (rSS), a previous meta-analysis has shown that patients with a higher rSS have increased mortality after TAVI, suggesting the negative impact of incomplete coronary revascularisation. [ 8 , 45 ] Although these findings are contradictory and should be evaluated in the context of the presence of ischaemia, it is important to provide complete revascularisation in such patients undergoing TAVI, at least in the main vessels/territories. [ 46 ]…”
Section: Intervention In Tavi Patientsmentioning
confidence: 99%